INSOLVENCY TEST AS EVIDENCE IN SHARIA BANKRUPTCY CASES - suhartono, suhartono (Universitas Muhammadiyah Surabaya, 2024)
The Indonesian bankruptcy law does not make insolvency a primary requirement for bankruptcy decision-making. Bankruptcy is based on the fulfillment of cumulative elements stipulated in Article 2 of the Bankruptcy and Suspension of Debt Payment Obligations Law (UUK-PKPU), even if the debtor is still solvent. This contrasts with Sharia bankruptcy, which places insolvency as a crucial substance in bankruptcy. This research is normative legal research with a substantive analysis approach. The results show that applying an insolvency test as evidence in Sharia bankruptcy cases is urgent and becomes a primary condition for upholding the ethics and fundamental principles of Sharia economic dispute resolution. In Islamic economics, bankruptcy (taflis) is the last resort (ultimum remedy) to resolve all disputes.